The devil's half acre: the untold story of how one woman liberated the South's most notorious slave jail - Green, Kristen (Seal Press)
Chosen ones -- "That which is brought forth follows the womb" -- The thing we can't name -- So well acquainted -- Anthony Burns and the Fugitive Slave Act -- Leaving the South -- Richmond families in Philadelphia -- Capital of the Confederacy -- After the war -- "God's half acre."